2009
DOI: 10.1002/term.186
|View full text |Cite
|
Sign up to set email alerts
|

Bone healing performance of electrophoretically deposited apatite–wollastonite/chitosan coating on titanium implants in rabbit tibiae

Abstract: Bone healing of tibial defect in rabbit model was used to evaluate a composite coating of apatite-wollastonite/chitosan on titanium implant. This coating has been developed to overcome the shortcomings, such as implant loosening and lack of adherence, of uncoated titanium implant. An electrophoretic deposition technique was used to coat apatite-wollastonite/chitosan on titanium implants. The present study was designed to evaluate the bone response of coated as compared to uncoated titanium implants in an anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…36 The polysaccharides were coated on titanium directly or in cooperation with other molecules such as collagen I, 13 18-21 29 collagen II, 16 calcium phosphate, 32 gelatine 34 and silk fibroin 35 (Tables II and III).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…36 The polysaccharides were coated on titanium directly or in cooperation with other molecules such as collagen I, 13 18-21 29 collagen II, 16 calcium phosphate, 32 gelatine 34 and silk fibroin 35 (Tables II and III).…”
Section: Resultsmentioning
confidence: 99%
“…The animal polysaccharides used for surface modifications were chitosan, which was investigated by in vitro studies, [30][31][32][33][34][35] and in vivo studies. 36 The polysaccharides were coated on titanium directly or in cooperation with other molecules such as collagen I, 13 18-21 29 collagen II, 16 calcium phosphate, 32 gelatine 34 and silk fibroin 35 (Tables II and III).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioactivity studies showed that CHIT enhanced the apatite formation rate in SBF, and apatite particles formed in SBF showed sheet-like morphology. It was also shown that AW/CHIT coatings exhibited good adhesion to Ti substrates and haemocompatibility (Sharma et al 2009a,b), as well as faster bone healing when implanted in rabbit tibiae (Sharma et al 2009c). …”
Section: Chitosan-based Nanocompositesmentioning
confidence: 99%
“…CS/CMC scaffolds containing bioactive glass have also been reported for bone tissue engineering applications [17]. Wollastonite (WS) or calcium silicate is a silicon based ceramic particle and is biocompatible, biodegradable and bioactive in nature [18][19][20]. Mesoporous particles are found to possess high specific surface area and pore volume which significantly improved the kinetic process of apatite formation on their surface thereby exhibiting better bioactivity [21,22] Biomaterial interaction with cell could activate intracellular signaling components/regulators resulting in osteogenesis.…”
Section: Introductionmentioning
confidence: 98%